ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIK SISWA SMP PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Rina Astuti; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
This research is a qualitative descriptive study that aims to analyze the level of mathematical communication skills of students in solving problems in the material of two-variable linear equation system with the categorization of the level of high, medium and low mathematical communication skills. The subjects in this study were eighth grade students as many as 24 people. The form of data collection is giving 5 items written test questions and interviews with selected subjects. Based on the results of the analysis, the average value of all instrument questions mathematical communication skills gained 43% for indicators linking images to mathematical ideas, 44% for indicators of constructing conjectures, formulating arguments, formulating definitions and generalizations, 21% for indicators stating ideas, situations and mathematical relations with images, 31% for indicators state mathematical situations or daily events into mathematical models, and 27% for indicators explain and make questions from mathematical problems so that if they are totaled and averaged 44%. Then the mathematical communication skills of class VIII junior high school students in the two variable linear equation material are low.